Uma história inconsistente de excreção de cálculos num adolescente: um caso clínico de Transtornos Autoinduzidos - Susana Correia Oliveira; Francisca Dias Freitas; António Maurício Fonseca; Ricardo Ramires; Cláudia Tavares (Sociedade Brasileira de Pediatria, 2023)
INTRODUCTION: Urolithiasis is uncommon in children. Suspicion should be raised in the presence of exaggerated clinical manifestations. CASE REPORT: An eleven-year old uncircumcised adolescent male was referred to a pediatric nephrology consultation complaining of recurrent episodes of dysuria with emission of black calculus. He had no lumbar or abdominal pain, nor gross hematuria. On physical examination, Giordano sign was negative bilaterally. His laboratory evaluation, urinalysis and ultrasound were unremarkable. A 24-hour urine collection had no noteworthy alterations. Stone analysis was unconclusive. No metabolic or infectious cause for a calculus was identified. The calculus was sent to an outside laboratory and rubber elastomer was detected. After determining the stones were self-induced, the adolescent was referred to Pedopsychiatry appointment. No further signs or symptoms of nephrolithiasis were reported. DISCUSSION: Although Factitious Disorders caused by proxy have been increasingly recognized, there is a significant less awareness that children and adolescents can intentionally falsify symptoms.